Spatio-temporal variations in the siphonophore community of the northern South China Sea - 李开枝 尹健强 黄良民 练树民 张建林 (Chinese journal of oceanology and limnology, 2013)
To understand how hydrological and biological factors affect near- to off-shore variations in the siphonophore community, we sampled zooplankton at 82 stations in the northern South China Sea during summer, winter, and spring. Forty-one species of siphonophore were collected by vertical trawling. The species richness of siphonophores increased from the nearshore to offshore regions in all three seasons of investigation, with maximum richness in summer and minimum richness in winter. The abundance of siphonophores was also higher in summer than in spring and winter, concentrated in the nearshore region in the warm season and scattered in the offshore region in the cold season. Four siphonophore groups were classified according to the frequency of occurrence: nearshore, near-offshore, offshore, and tropical pelagic. Among them, the nearshore group had higher abundance nearshore compared with the offshore. The tropical pelagic group had higher species number offshore than nearshore. Spatial and temporal fluctuations in taxonomic composition and abundance of siphonophores were due to the influence of the coastal upwelling and surface ocean currents of the South China Sea, driven by the East Asia monsoonal system.